(untitled) (Iranian Journal of Kidney Diseases, 2022)
SARS-CoV-2 vaccines are being administered worldwide. Most of the reported side effects are mild and self-limiting with few reported cases of severe adverse reactions. Here we report a case of acute cellular rejection in a kidney transplant recipient following vaccination with an inactivated SARS-CoV-2 vaccine. fifty- one years old man with autosomal dominant polycystic kidney disease, who had received a kidney transplantation from a living related donor, 3 years ago, presented with an impaired kidney function seven days after receiving the first dose of Sinovac’s COVID-19 vaccine. Kidney transplant biopsy revealed acute cellular rejection. The allograft function completely recovered after treatment with steroids. The analysis and investigation of the complications and adverse reactions induced by anti-COVID-19 vaccines, could increase our understanding of the underlying pathogenesis. DOI: 10.52547/ijkd.6915